2009
DOI: 10.1111/j.1744-1609.2009.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of systematic reviews about the efficacy of non-pharmacological interventions to improve sleep quality in insomnia

Abstract: Background  Insomnia is a very common condition in various populations. Non-pharmacological interventions might offer (safe) alternatives for hypnotics. Aim  To evaluate the evidence for efficacy from systematic reviews about non-pharmacological interventions to improve sleep quality in insomnia by a systematic review of systematic reviews and meta-analyses. Search strategy  Search strategies were conducted in the Database of Abstracts of Reviews of Effects (2002-July 2008), The Cochrane Database of Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…The results from this search were combined with the results from 2 reviews of reviews of the topic (85,86). As well as the many descriptive systematic reviews in this area, quantitative meta-analyses have found behavioral interventions for sleep to be efficacious in children (87), CBT-i to be moderately efficacious for anxiety symptoms (88), and CBT-i to be efficacious when delivered in computerized or groupbased formats (89,90).…”
Section: Reviewmentioning
confidence: 99%
“…The results from this search were combined with the results from 2 reviews of reviews of the topic (85,86). As well as the many descriptive systematic reviews in this area, quantitative meta-analyses have found behavioral interventions for sleep to be efficacious in children (87), CBT-i to be moderately efficacious for anxiety symptoms (88), and CBT-i to be efficacious when delivered in computerized or groupbased formats (89,90).…”
Section: Reviewmentioning
confidence: 99%
“…The past few decades have given rise to a handful of such studies in several clinical areas including lifestyle interventions,4 interventions to improve mental health,5 homeopathy,6 medical education,7 spinal manipulation,8 sleep medicine,9 and cancer,10 among others. Each of these reviews of reviews is focused on a specific clinical question.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing sleep disorders could improve performance and the general health of the athlete 111. Psychological strategies including CBT,119 self-hypnosis120 and mindfulness-based stress reduction121 show significant potential to improve sleep in non-athletes. CBT for insomnia has demonstrated efficacy 122–124.…”
Section: Non-pharmacological Pain Management Strategies In Elite Athlmentioning
confidence: 99%